Allocation of Interferon Gamma mRNA Positive Cells in Caecum Hallmarks a Protective Trait Against Histomonosis - Kidane, Fana Alem; Mitra, Taniya; Wernsdorf, Patricia; Hess, Michael; Liebhart, Dieter (Frontiers in Immunology, 2018)
Histomonosis is a parasitic disease of gallinaceous birds characterized by necrotic lesions in caecum and liver that usually turns fatal in turkeys while it is less severe in chickens. Vaccination using in vitro attenuated Histomonas meleagridis has been experimentally shown to confer protection against histomonosis. The protective mechanisms that underpin the vaccine-induced immune response are not resolved so far. Therefore, the actual study aimed to evaluate the location and quantitative distribution patterns of signature cytokines of type 1 (IFN-γ) or type 2 (IL-13) immune responses in vaccinated or infected hosts. An intergroup and interspecies difference in the spatial and temporal distribution patterns of cytokine mRNA positive cells was evident. Quantification of cells showed a significantly decreased percentage of IFN-γ mRNA positive cells at 4 days post-inoculation (DPI) in caeca of turkeys inoculated exclusively with the attenuated or the virulent inocula, compared to control birds. The decrement was followed by a surge of cells expressing mRNA for IFN-γ or IL-13, reaching a peak of increment at 10 DPI. In contrast, turkeys challenged following vaccination showed a slight increment of caecal IFN-γ mRNA positive cells at 4 DPI after which positive cell counts became comparable to control birds. The increase in infected birds was accompanied by an extensive distribution of positively stained cells up to the muscularis layer of caecal tissue whereas the vaccine group maintained an intact mucosal fold. In chickens, the level of changes of positive cells was generally lower compared to turkeys. However, control chickens were found with a higher percentage of IFN-γ mRNA positive cells in caecum compared to their turkey counterparts indicating a higher resistance to histomonosis, similar to the observation in immunized turkeys. In chickens, it could be shown that the changes of cytokine-positive cells were related to variations of mononuclear cells quantified by immunofluorescence. Furthermore, gene expression measured by RT-qPCR confirmed variations in organs between the different groups of both bird species. Overall, it can be concluded that a proportionally increased, yet controlled, allocation of IFN-γ mRNA positive cells in caeca hallmarks a protective trait against histomonosis.